Pengaruh Persepsi Manfaat dan Persepsi Kemudahan Terhadap Minat Menggunakan E-Wallet dan Persepsi Kemudahan Dimediasi oleh Kepercayaan (Kasus Di Provinsi Daerah Istimewa Yogyakarta) - Novitawati, Jessica; Algifari, Algifari (Universitas Negeri Semarang, 2023)
The aims of this study is to examine the effect of perceived usefulness and perceived ease of use on interest in using e-wallet of the people of province DIY. This study also examines the ability of trust to mediate the effect of perceived ease on the interest of the people of DIY in using e-wallet. The population in this study is the people who using e-wallet in the province of DIY. The sampling technique used purposive sampling method with a total sample of 107 respondents. Data collection in this study used a questionnaire distributed in the form of a Google Form with the criteria of respondents being aged 20 to 40 years and had used e-wallet for transactions. The hypothesis in this study was tested using the Macro Hayes model in the SPSS program. The results of this study indicate that perceived usefulness and perceived ease have a positive effect on interest in using e-wallet. Trust is able to mediate the effect of perceived ease on interest in using e-wallet people in the province of DIY.